Delivering Road Safety in India : Leadership Priorities and Initiatives to 2030 - World Bank (World Bank, Washington, DC, 2020)
India has the world’s highest reported number of annual road crash fatalities. According to the World Health Organization, road crash fatalities in India account for approximately 11 percent of the estimated 1.35 million global toll each year. Vulnerable road users, primarily pedestrians, cyclists, and two-wheelers, account for almost 54 percent of all fatalities and serious injuries. The young, working-age population is predominantly aff ected. Road users between the ages of 18 and 45 comprise 69 percent of all fatalities. This disproportionate impact of road crash mortality and morbidity on this economically productive segment of the population has a negative impact on productivity and is likely to signifi cantly depress GDP growth rates.